Distribution, richness and conservation of troglobitic fishes from Serra da Bodoquena, MS (Teleostei) - Cordeiro, Lívia Medeiros; Borghezan, Rodrigo; Trajano, Eleonora (Revista da Biologia, 2018)
In Bodoquena karst area occur large submerged and flooded cave systems, as well as dry caves, which harbor an important troglobitc fauna. Five troglobitic species of Siluriformes are currently known: Ancistrus formoso (Loricariidae), Trichomycterus dali (Trichomycteridae), and three undescribed species, Ancistrus sp. n. (Loricariidae), Rhamdia sp.n. (Heptapteridae) and Trichomycterus cf. dali. Due the need of understanding the ecological, biological and biogeographic processes for the development of effective actions on conserve the subterranean ecosystems, partial results of population studies of the three undescribed species are presented. The expansion of conservation areas in order to cover all the occurrence areas of troglobitic fishes in Bodoquena Plateau is suggested.